Pengembangan Media E-Pop untuk Meningkatkan Kemampuan Membaca Permulaan Anak Usia 5-6 Tahun - Rahmatun Nisa; Rita Kurnia; Enda Puspitasari (Journal on Education, 2023)
The purpose of this study was to determine the development and suitability of electronic media to improve early reading skills in children aged 5-6 years. The research method used is Research and Development (RnD) which produces products and can test the effectiveness of products. The data analysis technique used by researchers inthis study is a quantitative descriptive analysis technique. Analysis of product feasibility data is carried out by valuating the results determined by learning media experts and material experts in the form of a questionnaire (questionnaire). The resulting development product is in the form of e-pop media consisting of an electrical circuit controlled by the Android system and packaged in a box as a learning tool to develop early reading skills for children aged 5-6 years. The data analysis technique used is a quantitative descriptive analysis technique. from the research it can be concluded that the validation of material experts is 88% "very feasible", the validation of media experts is 87% "very feasible" and the validation of educators is 96% "very feasible". The percentage of results of limited trials conducted was 89%. The results of the study show that e-pop media can be used as a learning tool to improve the beginning reading skills of children aged 5-6 years.